The Prevalence, Characteristics, and Factors Associated with Chinese Herbal Medicine Use Among Chinese Middle-Aged and Older Adults with Chronic Lung Disease: A Cross-Sectional Study - Tian H; Zhu X; Liu H; Liao Y; Cui K; Liu J; Gong X (Journal of Multidisciplinary Healthcare)
Hui Tian,* Xiaorong Zhu,* Hongwang Liu, Yangfang Liao, Kaiwang Cui, Jianping Liu, Xiangwen Gong Department of Respiratory and Critical Care Medicine, Ganzhou Key Laboratory of Respiratory Diseases, Ganzhou Institute of Respiratory Diseases, the Fifth People’s Hospital of Ganzhou, Ganzhou, Jiangxi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiangwen Gong; Jianping Liu, Department of Respiratory and Critical Care Medicine, The Fifth People’s Hospital of Ganzhou, Dongjiangyuan Road 666, Zhanggong District, Ganzhou, Jiangxi Province, 341000, People’s Republic of China, Email gzwyhys@126.com; gzwyhxk@126.comPurpose: Identifying factors that influence Chinese herbal medicine (CHM) use in chronic lung disease (CLD) patients can inform targeted strategies to boost CHM use. However, the prevalence and factors affecting CHM use for treating CLD in middle-aged and older Chinese patients remain understudied. This study aims to examine the prevalence and influencing factors of CHM use among middle-aged Chinese patients with CLD.Patients and Methods: The data analyzed in this study were extracted from the China Health and Retirement Longitudinal Study in 2018. A cross-sectional analysis of 2784 participants aged 45 years and older taking CHM for CLD was included, and influencing factors (demographic characteristics, health status, and healthcare service use) predicting the use of CHM for CLD were identified through multivariate logistic regression model.Results: The prevalence of using CHM to treat CLD was 22.4% (624/2784). Compared to participants with CLD who did not use CHM, those with CLD who used CHM were more likely to be female, and non-smoking, non-drinking, purchased insurance (OR=2.35; 95% CI=1.09, 5.04), went to a traditional Chinese medicine hospital (OR=3.5; 95% CI=1.96, 6.25) and self-treatment (OR=1.67; 95% CI=1.33, 2.10), the health status being poor (OR =1.74; 95% Cl=1.18, 2.56), asthma (OR=1.55; 95% Cl=1.16, 2.09) and depression (OR =1.42; 95% Cl=1.14, 1.75). In the additive interaction analysis, patients who tend to self-medicate and with depression were most likely to use CHM (OR=2.52; 95% Cl=1.85, 3.42).Conclusion: A considerable middle-aged and older Chinese patient with CLD uses CHM for treatment. Multiple factors can influence CHM use, particularly self-treatment and depression.Keywords: influencing factors, Chinese herbal medicine, chronic lung disease, Chinese, middle-aged and older adults, cross-sectional study